PERKEMBANGAN MOTORIK KASAR PADA BAYI 6-12 BULAN YANG ASI EKSLUSIF DAN NON ASI EKSKLUSIF DI WILAYAH PUSTU DESA DELIK KECAMATAN PELALAWAN TAHUN 2019 - Ekry Binti Farizal (Jurnal Kesehatan Husada Gemilang, 2019)
Breast milk (ASI) is a liquid food that serves to meet the baby’s needs for various nutrients and nutritional substances needed for growth and development and to meet the baby’s need for energy. Exclusive breastfeeding is given to at least until the baby is months old. There are several factors influence baby’s growth and development, one of which is nutritional intake that is supplied by giving exclusive breastfeeding. The development ability of mental and motor especially gross motor of children correlate with the concentration of taurine during infancy. This study is to clarify whether any differences in the development of baby’s gross motor between those who are given exclusive and non-exclusive breastfeeding. The design of the research was observation. The population and sample of the research were 60 respondents that are taken over total sampling. KPSP questionnaire sheet (Pre-Screening Development Questionnaire) was used to distinguish the development of the respondents. The data obtained were processed thru the SPSS and analyzed through univariate and bivariate analysis. The results demonstrate the differences of the development of the baby’s gross motor that those are given exclusive and non-exclusive breastfeeding by using T-test (p=0.00 or <0.05). It is highly expected that health workers could provide more information or counselling about the differences of baby’s gross motor development that those are given exclusive and nonexclusive breastfeeding in Polindes of Delik, District of Pelalawan.